SAT0344 Intravenous Bisphosphonate Reduces Rapidly Pain in Complex Regional Pain Syndrome (CRPS). (10th June 2014) - Bartoli, F.; Fiori, G.; Peruzzi, F.; Guidi, G.; Pfanner, S.; Ceruso, M.; Matucci Cerinic, M.
Abstract : Background: The treatment of CRPS remains controversial, but multidisciplinary and interdisciplinary approaches is mandatory to prevent long-standing or permanent disability. Bisphosphonates, apart from their antiresorptive activity, have been shown to have an analgesic or anti-inflammatory effect. Bisphosphonate therapy has been suggested for the therapy for CRPS. Objectives: to evaluate the efficacy of intravenous bisphosphonates in reducing pain in patients with CRPS. Methods: 52 patients (14 males and 38 females; mean age 64.3±8 years) diagnosed with CRPS of carpal and metacarpals bones (confirmed by clinical, x-ray and MRI) from two to six weeks, previously treated with non-steroidal anti-inflammatory drugs (NSAID), calcium, Vitamin D, physical therapy. All patients were treated with iv clodronate 300 mg/day for 2 weeks, followed by im clodronate 200 mg/weekly for 3 months. Pain scale (VAS 0-100) and joint examination were performed before, after two weeks and after 3 months of clodronate therapy. X-ray and MRI were performed at the diagnosis and after 3 months. Results: Clodronate reduced pain significantly (p=0.0001) after two weeks of therapy (87.7±8 mm vs 15.7±4 mm). After 3 months, a further reduction of pain (10.4±3 mm) was found (p<0.001). After two weeks of therapy reduction of pain was associated also to a reduction of hyperhidrosis, edema and joint stiffness. X-ray showed a stability of radiological features, and MRI a significant reduction of bone oedema. No adverse events were reported. Conclusions: Iv clodronate achieves a rapid reduction of pain in patients with CRPS. Early intervention and reduction of pain is associated with a rapid clinical and imaging improvement, may prevent long-standing disability. References: Tran de QH, Duong S, Bertini P, Finlayson RJ. Treatment of complex regional pain syndrome: a review of the evidence. Can J Anaesth. 2010 Feb;57(2):149-66. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4175